CD103(+) Kidney Dendritic Cells Protect against Crescentic GN by Maintaining IL-10–Producing Regulatory T Cells - Evers, Beatrix D.G. (J Am Soc Nephrol, 2016)
Kidney dendritic cells (DCs) regulate nephritogenic T cell responses. Most kidney DCs belong to the CD11b(+) subset and promote crescentic GN (cGN). The function of the CD103(+) subset, which represents <5% of kidney DCs, is poorly understood. We studied the role of CD103(+) DCs in cGN using several lines of genetically modified mice that allowed us to reduce the number of these cells. In all lines, we detected a reduction of FoxP3(+) intrarenal regulatory T cells (T(regs)), which protect against cGN. Mice lacking the transcription factor Batf3 had a more profound reduction of CD103(+) DCs and T(regs) than did the other lines used, and showed the most profound aggravation of cGN. The conditional reduction of CD103(+) DC numbers by 50% in Langerin-DTR mice halved T(reg) numbers, which did not suffice to significantly aggravate cGN. Mice lacking the cytokine Flt3L had fewer CD103(+) DCs and T(regs) than Langerin-DTR mice but exhibited milder cGN than did Batf3(−/−) mice presumably because proinflammatory CD11b(+) DCs were somewhat depleted as well. Conversely, Flt3L supplementation increased the number of CD103(+) DCs and T(regs), but also of proinflammatory CD11b(+) DCs. On antibody-mediated removal of CD11b(+) DCs, Flt3L supplementation ameliorated cGN. Mechanistically, CD103(+) DCs caused cocultured T cells to differentiate into T(regs) and produced the chemokine CCL20, which is known to attract T(regs) into the kidney. Our findings show that CD103(+) DCs foster intrarenal FoxP3(+) T(reg) accumulation, thereby antagonizing proinflammatory CD11b(+) DCs. Thus, increasing CD103(+) DC numbers or functionality might be advantageous in cGN.